In Silico Study Potential Secondary Metabolite Candidate of Citronella Grass (Cymbopogon nardus) on Immunity Cases - Veda, Adella Infia Helga; Muchlisin, M. Artabah; Jamil, Ahmad Shobrun; Almutahrihan, Irsan Fahmi; Satriawan, Herland (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Foreign invaders in the form of bacteria, fungi, or viruses can cause various diseases if they enter the body, both molecularly and cellularly. Hence, the body needs a compound that can maintain and enhance the immune and immune systems to recognize abnormal cells that can become a source of disease for the body. Improving immunity/resistance for people with diseases is very important so that people undergoing treatment are given immunostimulant drugs or pharmaceutical preparations. This study aimed to determine the protein network associated with the body's immune system, which was activated by the administration of citronella (Cymbopogon nardus). The research method used is explorative descriptive with in silico analysis using a computational model with software including KNApSAck, Dr. Duke, Pubchem, Swiss ADME, Swiss Target Prediction, Gene Cards, Venny, STRING, and KEGG. Based on the results of pharmacological network analysis, C. nardus contains 40 secondary metabolites, 25 of them have high bioavailability. Based on pharmacological network analysis, (-)-menthol is an important compound that plays a role in the immune system because it is expected to interact with three crucial pathways related to immunomodulators.